PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL: KOMITMEN ORGANISASI DAN PERSEPSI INOVASI SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Satuan Kerja Instansi Vertikal Wilayah Pembayaran Kantor Pelayanan Perbendaharaan Negara Sampi - Eka Yudha Utama; Abdul Rohman (Diponegoro Journal of Accounting, 2013)
The main purpose of this study is to examine the budgetary participation and managerial performance relationship in a public sector organization. Its also attempts to examine whether organization commitment and perception of innovation mediate the budgetary participation and managerial performance relationship. This study used data obtained from public sector organization in working area of Sampit Treasury office. Survey questionnaires are used to collect data of this study. From 143 questionnaires was given to managers in a public sector organization, 86 questionnaire (60,14%) were received back and 57 questionnaire (39,86%) complete and can be processed with Path Analysis Technique using IBM SPSS v16 Program. The analysis result show that budgetary participation and managerial performance have positive relationship and statistically significant. Budgetary participation directly affect organizational commitment and perception of innovation. Organizational commitment and managerial performance have positive relationship but statistically not significant. Perception of innovation and managerial performance have positive relationship and statistically significant. But budgetary participation did not affect managerial performance via the intervening variables of organizational commitment and perception of innovation.